Culture: A factor of Political Life in Arab Islamic Societies (Czech Journal of International Relations, 2002)
Any study of society, including an analysis of politics and international relations, must pay due attention to all factors. Culture, of course, is one of the fundamental determinants of any social life. Full comprehension of the internal organisation, links, inner processes and behaviour of a community or any of its members to other communities and international actors is impossible without the knowledge and understanding of its culture. This essay explores some typical features of Arab Islamic culture systems which help to explain some of what we encounter in today's Middle East: suicide bombings by Islamic radicals, spurts of violence, intransigence in negotiations, unwillingness to reach a compromise, etc. The author concentrates on some of the traditional values of Arab and Islamic societies and on Islam as the dominant religion in the region.